Easy Preparation of Zinc Molybdate Photocatalyst and Its Application for Degradation of Methylene Blue - Bakri, Ridla; Firmansyah, Rika; Yulizar, Yoki (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2023)
Photocatalyst is one way that can be done to overcome the problem of dye waste in water. Hazardous chemicals are regularly used in the manufacture of photocatalysts. In this research, ZnMoO4 was prepared by an environmentally friendly and cost-effective synthesis. The functional groups, crystalline structure and morphology of ZnMoO4 were characterised using fourier transform infrared (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and transmission electron microscopy (TEM). The band gap energy has been studied through UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS). The photocatalytic activity of ZnMoO4 was tested against the organic pollutant methylene blue under visible light irradiation and its degradation products were analyzed with a UV-Vis spectrophotometer at a wavelength of 664 nm. The photocatalytic process of ZnMoO4 has been able to degrade 99% of methylene blue after 80 minutes of irradiation. The excellent photodegradation performance indicates that the transition activity of electron currents from the valence band to the conduction band on ZnMoO4 is going well.